Review of the Cenozoic Floras and Vegetation of Greece - Velitzelos, Dimitrios; Bouchal, Johannes M; Denk, Thomas (Review of Palaeobotany and Palynology)
Oligocene to Pleistocene floras of Greece are reviewed based on published and unpublished material. Oldest plant-bearing sediments of Rupelian-Chattian age are exposed in eastern Thrace (Evros) and were deposited after the closure of the Turgai Seaway. They contain a blend of (i) taxa that migrated to western Eurasia from the East (Alnus, Fagus), (ii) characteristic Oligocene taxa (Nyssa altenburgensis, Ampelopsis hibschii), and (iii) extinct (Eotrigonobalanus, Quasisequoia) and modern genera (Calocedrus, Quercus Group Lobatae) from older epochs. Coastal palm swamps and laurel forests of the hinterland indicate a subtropical, fully humid to winter-dry climate (Cfa, Cwa according to Köppen). The Aquitanian-Burdigalian plant assemblage of Lesbos is intermediary between Evros and the Burdigalian floras of Euboea sharing taxa with Evros (palms), and with Euboea and early Miocene floras of Anatolia (Güvem, Tilia). In the early Miocene (Burdigalian) floras of Euboea, species of Quercus Group Ilex (Q. drymeja, Q. mediterranea) characteristic of fully humid or winter-dry (monsoon) climates (Cf, Cw) became dominant elements in well-drained forests. Floristic links are with late Oligocene to middle Miocene floras of Central Asia (Tilia), Asia Minor (cycads, Quercus Group Ilex, Tilia), and South and Central Europe (cycads, Quercus Group Ilex, palms). Middle Miocene floras are restricted to the Aegean islands (Chios). Biogeographic links are with early to late Miocene floras of Central Europe (Parrotia, Podocarpium) and with middle Miocene floras of Anatolia (Parrotia). Upper Miocene plant-bearing sedimentary formations are most abundant in Greece and exposed on the Ionian Islands, Greece mainland to East Macedonia, Peloponnese, Aegean Islands, and Crete. Overall, the fossil plant assemblages from Greece mainland are indicative of fully humid conditions during this time (Cfa), with Fagus and oaks of Quercus Group Ilex being dominant elements. Seasonality may have been more pronounced on the Peloponnese and the Aegaean Islands and Crete, expressed by the rare occurrence of Fagus in the fossil records of these areas. The palaeobotanical records from Samos unambiguously point to the presence of forest vegetation during early Tortonian to Messinian (Cwa) when the famous vertebrate faunas of Samos were deposited. The Pliocene is characterized by the regional occurrence of modern types of deciduous oaks mainly of Quercus Group Cerris and Quercus subsect. Galliferae. East Asian links persist in Fagus, Quercus, and Cupressaceae, North American ones in Sabal; several other mesophytic taxa from previous periods are recorded as well. The modern sclerophyllous Mediterranean vegetation, thriving in a warm summer dry climate (Csa), cannot be traced prior to the Pleistocene based on the palaeobotanical record.
Keywords: Cenozoic; Eastern Mediterranean; greece; landscape evolution; Mediterranean climate; plant evolution

Light transmissivity of tube shelters affects root growth and biomass allocation of Quercus ilex L. and Pinus halepensis Mill - de Castro, Alberto Vázquez; Oliet, Juan A.; Puértolas, Jaime; Jacobs, Douglass F.; Puértolas, Jaime; Jacobs, Douglass F. (ANNALS OF FOREST SCIENCE, 2014)
Context Tube shelters have been shown to enhance field performance of several Mediterranean species, but responses of newly planted seedlings to the microenvironment induced by shelter walls with different light transmissivity are still poorly documented. Aims We studied effects of a range of shelters with varying light transmissivity on post-planting seedling responses during the wet season establishment phase for two Mediterranean trees of contrasting functional ecology. Methods Root growth, biomass allocation, water potential, and chlorophyll fluorescence of Quercus ilex and Pinus halepensis seedlings were evaluated across shelters varying in light transmissivity (80, 40, 20, and 10 % plus a mesh shelter) with irrigation. Results Plants in dark tubes (20 and 10 % light transmissivity) had less above-and belowground growth and more than two times greater leaf to protruding roots mass ratio, with shoot growth response of Q. ilex being less plastic. Ratio of leaf area/protruding roots area decreased when light transmissivity increased, although no differences were found at >= 40 % transmissivity. Xylem water potential indicated lack of water stress, and high maximum photosynthetic efficiency (F-v/F-m) values show no photoinhibition symptoms irrespective of light transmissivity. Conclusion Shelter transmissivity >= 40 % promotes rapid and vigorous root growth immediately after planting for these species. This minimum transmissivity should be considered as a target when designing shelters to help root development and improve water balance of Mediterranean seedlings.
Keywords: Aleppo pine; chlorophyll fluorescence; Forest restoration; Holm oak; Light ambient response; Mediterranean climate; Transplanting performance; Treeshelters

Strong functional stability of soil microbial communities under semiarid Mediterranean conditions and subjected to long-term shifts in baseline precipitation - Curiel Yuste, J; Fernandez-Gonzalez, a.J. J; Fernandez-Lopez, M; Ogaya, R; Penuelas, J; Sardans, J; Lloret, F (Soil Biology and Biochemistry, 2014)
Abstract We investigated the effect of soil microclimate on the structure and functioning of soil microbial communities in a Mediterranean Holm-oak forest subjected to 10 years of partial rain exclusion manipulations, simulating average drought conditions expected in Mediterranean areas for the following decades. We applied a high throughput DNA pyrosequencing technique coupled to parallel measurements of microbial respiration (RH) and temperature sensitivity of microbial respiration (Q10). Some consistent changes in the structure of bacterial communities suggest a slow process of community shifts parallel to the trend towards oligotrophy in response to long-term droughts. However, the structure of bacterial communities was mainly determined by short-term environmental fluctuations associated with sampling date (winter, spring and summer) rather than long-term (10 years) shifts in baseline precipitation. Moreover, long-term drought did not exert any chronic effect on the functioning of soil microbial communities (RH and Q10), emphasizing the functional stability of these communities to this long-term but mild shifts in water availability. We hypothesize that the particular conditions of the Mediterranean climate with strong seasonal shifts in both temperature and soil water availability but also characterized by very extreme environmental conditions during summer, was acting as a strong force in community assembling, selecting phenotypes adapted to the semiarid conditions characterizing Mediterranean ecosystems. Relations of climate with the phylogenetic structure and overall diversity of the communities as well as the distribution of the individual responses of different lineages (genera) to climate confirmed our hypotheses, evidencing communities dominated by thermotolerant and drought-tolerant phenotypes.
Keywords: Adaptation; CO2; diversity; Extreme events; functional stability; Mediterranean climate; Soil bacterial communities

Assessing ozone and nitrogen impact on net primary productivity with a Generalised non-Linear Model. - De Marco, Alessandra; Screpanti, Augusto; Attorre, Fabio; Proietti, Chiara; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2013)
Some studies suggest that in Europe the majority of forest growth increment can be accounted for N deposition and very little by elevated CO(2). High ozone (O(3)) concentrations cause reductions in carbon fixation in native plants by offsetting the effects of elevated CO(2) or N deposition. The cause-effect relationships between primary productivity (NPP) of Quercus cerris, Q. ilex and Fagus sylvatica plant species and climate and pollutants (O(3) and N deposition) in Italy have been investigated by application of Generalised Linear/non-Linear regression model (GLZ model). The GLZ model highlighted: i) cumulative O(3) concentration-based indicator (AOT40F) did not significantly affect NPP; ii) a differential action of oxidised and reduced nitrogen depositions to NPP was linked to the geographical location; iii) the species-specific variation of NPP caused by combination of pollutants and climatic variables could be a potentially important drive-factor for the plant species' shift as response to the future climate change.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23078996
Keywords: Generalized Linear/non-Linear Model; Mediterranean climate; Net primary productivity; Nitrogen deposition; Ozone

Foliar Symptoms Triggered by Ozone Stress in Irrigated Holm Oaks from the City of Madrid, Spain - Calderon Guerrero, Carlos; Guenthardt-Goerg, Madeleine S.; Vollenweider, Pierre (PLOS ONE, 2013)
Background: Despite abatement programs of precursors implemented in many industrialized countries, ozone remains the principal air pollutant throughout the northern hemisphere with background concentrations increasing as a consequence of economic development in former or still emerging countries and present climate change. Some of the highest ozone concentrations are measured in regions with a Mediterranean climate but the effect on the natural vegetation is alleviated by low stomatal uptake and frequent leaf xeromorphy in response to summer drought episodes characteristic of this climate. However, there is a lack of understanding of the respective role of the foliage physiology and leaf xeromorphy on the mechanistic effects of ozone in Mediterranean species. Particularly, evidence about morphological and structural changes in evergreens in response to ozone stress is missing. Results: Our study was started after observing ozone -like injury in foliage of holm oak during the assessment of air pollution mitigation by urban trees throughout the Madrid conurbation. Our objectives were to confirm the diagnosis, investigate the extent of symptoms and analyze the ecological factors contributing to ozone injury, particularly, the site water supply. Symptoms consisted of adaxial and intercostal stippling increasing with leaf age. Underlying stippling, cells in the upper mesophyll showed HR-like reactions typical of ozone stress. The surrounding cells showed further oxidative stress markers. These morphological and micromorphological markers of ozone stress were similar to those recorded in deciduous broadleaved species. However, stippling became obvious already at an AOT40 of 21 ppm.h and was primarily found at irrigated sites. Subsequent analyses showed that irrigated trees had their stomatal conductance increased and leaf life -span reduced whereas the leaf xeromorphy remained unchanged. These findings suggest a central role of water availability versus leaf xeromorphy for ozone symptom expression by cell injury in holm oak.
APSAPSThe following values have no corresponding Zotero field: pub-location: 1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111 USA publisher: PUBLIC LIBRARY SCIENCE
Keywords: Holm oak; Mediterranean climate; natural vegetation; Ozone; Stomatal uptake

Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

Organic C distribution and N mineralization in soil of oak woodlands with improved pastures - Gómez-Rey, Maria Xesús; Garcês, Ana; Madeira, Manuel (Revista de Ciências Agrárias, 2011)
Cork oak woodlands in Portugal are a multipurpose agroforestry system occurring in areas mostly degraded by former cereal crops and overgrazing. The objective of this study was to evaluate the effect of scattered cork oak trees (Quercus suber L.) on soil quality, considering two land use systems: unmanaged pastures and improved pastures. Soil samples were collected in a square grid around scattered cork oak trees to evaluate the spatial variability of soil bulk density and chemical properties. In soil samples taken beneath tree canopy and in the open, net N mineralization was evaluated by aerobic incubations. Also, laboratory incubations were carried out to evaluate the effect of roots (tree or/and herbaceous) and water solutions (bulk precipitation, throughfall or stemflow) on net N mineralization.Contents of organic C, total N and extractable P were increased beneath the tree canopy, and gradually decreased with the increase of distance to the tree trunk. Improved pastures established 26 years ago increased organic C (0.76 kg m-2), total N (0.06 kg m-2) and extractable P (2.70 g m-2) amounts in the 0-10 cm soil layer beneath the tree canopy relatively to those of unmanaged pastures. Net N mineralization was significantly greater (about 2 times) in soils beneath the tree canopy than in those of open areas. N mineralization was unaffected by addition of throughfall or stemflow, while a significant reduction resulted from tree roots addition, this effect being stronger for herbaceous plant roots than for tree roots. Maintenance of tree cover combined with permanent improved pastures should be considered to improve soil quality in oak woodlands of Southern Portugal.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: agroforestry systems; legumes; Mediterranean climate; soil quality.

The importance of mesophyll conductance in regulating forest ecosystem productivity during drought periods - KEENAN, Trevor; Sabaté, Santi; Gracia, Carlos (Global Change Biology, 2010)
Water availability is the most limiting factor to global plant productivity, yet photosynthetic responses to seasonal drought cycles are poorly understood, with conflicting reports on which limiting process is the most important during drought. We address the problem using a model-data synthesis approach to look at canopy level fluxes, integrating twenty years of half hour data gathered by the FLUXNET network across six Mediterranean sites. The measured canopy level, water and carbon fluxes were used, together with an inverse canopy ecophysiological model, to estimate the bulk canopy conductance, bulk mesophyll conductance, and the canopy scale carbon pools in both the intercellular spaces and at the site of carboxylation in the chloroplasts. Thus the roles of stomatal and mesophyll conductance in the regulation of internal carbon pools and photosynthesis could be separated. A quantitative limitation analysis allowed for the relative seasonal responses of stomatal, mesophyll, and biochemical limitations to be gauged. The concentration of carbon in the chloroplast was shown to be a potentially more reliable estimator of assimilation rates than the intercellular carbon concentration. Both stomatal conductance limitations and mesophyll conductance limitations were observed to regulate the response of photosynthesis to water stress in each of the six species studied. The results suggest that mesophyll conductance could bridge the gap between conflicting reports on plant responses to soil water stress, and that the inclusion of mesophyll conductance in biosphere–atmosphere transfer models may improve their performance, in particular their ability to accurately capture the response of terrestrial vegetation productivity to drought.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 16 june 2009; conductance limitations; Drought; FLUXNET; june 2009 and accepted; Mediterranean climate; mesophyll conduc-; mesophyll conductance; photosynthesis; received 12 march 2009; revised version received 2; tance; water stress

Vessel features of Quercus ilex L. growing under Mediterranean climate have a better climatic signal than tree-ring width - Campelo, Filipe; Nabais, Cristina; Gutiérrez, Emilia; Freitas, Helena; García-González, Ignacio (Trees, 2010)
We investigated whether vessel time series of Holm oak (Quercus ilex L.), a diffuse to semi-ring-porous species, can record a climatic signal which differs from the signal encoded in tree-ring width (TRW). The study was conducted in ten Q. ilex trees from a coppice stand in northeast Spain. Chronologies of TRW, mean vessel area (MVA) and maximum vessel area (MAX) were developed and correlated with climate data, for the period 1985–2004 (20 years). Our results indicate that vessel features contain environmental information that is different from that stored in TRW. MAX chronologies correlate better to early spring precipitation (April–May) than TRW chronologies, and so does MVA of the largest 20–25 vessels from the ﬁrst third of the ring with late spring precipitation (May–June). Also, the combination of MVA and TRW is a better predictor of summer precipitation. This explorative study clearly shows that vessel features can complement the climatic signal of TRW increasing the resolution of the climate reconstructions for the Mediterranean region.
Keywords: Dendrochronology; Holm oak; Mediterranean climate; Tree ring; Vessel features

A map of autumn precipitation for the third millennium BP in the Eastern Iberian Peninsula from charcoal carbon isotopes - Aguilera, M.; Espinar, C.; Ferrio, J. P.; Pérez, G.; Voltas, J. (Journal of Geochemical Exploration, 2009)
Carbon isotope composition (δ 13 C) in tree-rings has become routinely used in palaeoclimatic research for the assessment of changes in plant water availability in seasonally dry climates. However, the distribution of long tree-ring records around the world is very limited. Alternatively, the original climate signal of wood δ 13 C is well preserved in fossil charcoal and, accordingly, charcoal δ 13 C can be used to quantify past changes in water availability (e.g. precipitation). We report a case study on spatial palaeoclimate reconstruction which aims to characterize the transition between Bronze and Iron Ages, the so-called Iron Age Cold Epoch (ca. 900– 300 BCE), using charcoals of Quercus ilex/coccifera from a set of 11 contemporary archaeological sites of eastern Spain. Climatic inferences were obtained after calibrating a linear model predicting seasonal precipitation from δ 13 C of Q. ilex wood samples obtained across a rainfall gradient. The best regression model corresponded to September–December (autumn) precipitation (Paut ), in agreement with the fact that Q. ilex is able to exploit previous-year water reserves thanks to very effective water uptake. Subsequently, we estimated Paut from the δ 13 C of fossil charcoal to infer spatial patterns in water availability. Overall, estimated past Paut was about 19% higher (296 mm) than present-time values averaged across archaeological sites (249 mm). However, a clear geographic pattern of differences in precipitation could be observed in which the inner continental regions of eastern Spain were characterized by more humid conditions in the past, whereas the coastal strip of the Mediterranean Sea barely differed in past and present Paut values. The quite uniform distribution of archaeological sites over eastern Spain allowed development of contour maps of absolute and relative (to present) past Paut using gridded interpolation methods implemented in a GIS, highlighting the potential of this approach for reconstructing high-resolution spatial patterns of past climate
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Drought; GIS; Iron Age Cold Epoch; Isoscape; Late Holocene; Mediterranean climate; Quercus ilex

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.92910.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Leaf fluctuating asymmetry of Holm oak in response to drought under contrasting climatic conditions - Hódar, José a. (Journal of Arid Environments, 2002)
Fluctuating asymmetry (FA) can be defined as small, random deviations from bilateral symmetry in structures that, typically, are bilaterally symmetrical. In plants, FA has been used as a tool for monitoring levels of ecological stress. In this work, I analyse the FA response to drought in the Holm oak (Quercus ilex) in SE Spain, to test whether FA increases or diminishes when climatic conditions are more stressful. Leaves from three different cohorts, corresponding to one drought year (1995) and two wet years (1996 and 1997) were collected at five sites contrasting in rainfall conditions, from very low to rather high rainfall. In two of the zones, two different morphs of leaves were collected. Furthermore, one of the sites was chosen close to a river, to examine the effect of water enhancement in the trees during drought and post-drought conditions. The results revealed no differences in response to drought in terms of FA between leaf morphs. However, while plants from rainy sites showed a decline in leaf FA from drought to wet years, the water-enhanced site and the dry sites showed scant or negligible differences between years. There was a significant decrease in FA from rainy sites to dry sites. These results suggest that (1) plants living in the more stressful sites are more symmetrical, (2) the more symmetrical plants respond less to yearly variations in drought stress, and (3) the response to yearly variations in drought depend on the climatic conditions in which a tree is living
Keywords: Drought; Fluctuating asymmetry; Holm oak; Mediterranean climate; Quercus ilex; RAINFALL

A dendroclimatological approach to diameter growth in adult cork-oak trees under production - Costa, A.; Pereira, H.; Oliveira, A. (Trees, 2001)
The diameter growth of mature cork oaks under cork production in southwestern Portugal was studied during a 9-year cork-production cycle in relation to fluctuations in precipitation and temperature, and to drought indices combining the two variables. A dendroclimatological approach was applied to the series of 8 complete years contained in the cork-production cycle and growth effects were removed by standardization and calculation of annual growth indices. The most important factor positively influencing diameter growth was cumulative precipitation in the growing season (January–June) and in the previous autumn and winter (October/November of the previous year–June). The monthly temperature is a less influential factor, negatively correlated with diameter growth in high summer drought (August) and positively correlated at the beginning of physiological activity (March).
Keywords: climatic fluctuations; dendroclimatology; diameter growth; Mediterranean climate; Quercus suber L.

The dehesa system of southern Spain and Portugal as a natural ecosystem mimic - Joffre, R; Rambal, S; Ratte, J P (Agroforestry Systems, 1999)
The dehesas of the southwestern Iberian Peninsula are ‘man-made’ ecosystems characterised by a savannah-like physiognomy. The trees are viewed as an integrated part of the system, and as a result are planted, managed, and regularly pruned. Palynological and historical evidence of the manipulation of initial ecosystems by man to obtain a savannah-like ecosystem is presented. The ecological functions of the tree are detailed using results obtained at two complementary scales. At the local scale, strong soil structural differences and functional differences in water budget and patterns of water use are observed under and outside the tree canopy. Using the concept of ecosystem mimicry, the two coexistent components of dehesas can be compared to two distant stages of a secondary succession characterised by very different behaviours. At the regional scale, evidence of relationships between tree density and mean annual precipitation over more than 5000 km2 suggests that the structure of these man-made agroecosystems have adjusted over the long-term and correspond to an optimal functional equilibrium based on the hydrological equilibrium hypothesis. Finally, the future of dehesas in the face of contemporary exogenous threats of economic and global environmental origin is discussed. 1. Introduction
Keywords: hydrological equilibrium; Mediterranean climate; optimality; Quercus ilex; Quercus suber; water balance

Ecology and history of a wooded landscape in southern Spain - MARAÑÓN, T; Ojeda, J F (ECOLOGICAL HISTORY OF EUROPEAN FORESTS, 1998)
An extensive oak woodland, of about 1000 km(2), dominated by evergreen cork oak (Quercus suber) and semideciduous Q. canariensis, is found in southern Spain, near the Strait of Gibraltar, and contrasts with the paradigm of deforested Mediterranean mountains. Several factors, ecological, geographical and historical, have contributed to the origin and maintenance of this forested landscape. The rough relief and the acidic, nutrient-poor soils (derived from Oligo-Miocene sandstone) made this area unsuitable for cultivation. The oceanic influence favours the growth of oak trees. In particular, the cork oak is well suited to acidic soils and the humid Mediterranean climate. Three historical milestones seem relevant to the preservation of this woodland. Its location at a frontier during medieval times (thirteenth to fifteenth centuries) discouraged villages and reduced human pressure on the woodland resources. The rise of the value of cork helped to preserve the cork oak woodland during early nineteenth. century industrial times. contemporary consciousness about the conservation of woodland landscapes (somewhat unusual in the Mediterranean region) led to their designation as Los Alcornocales (meaning `The cork oak woodlands') Natural Park, devoted to the eco-development of the region.
Keywords: Cork oak; forest landscape; human pressure; Mediterranean climate; Oak woodlands; Quercus canariensis; Quercus suber

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Diez, P (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Díez, P. (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate

Stem xylem features in three Quercus (Fagaceae) species along a climatic gradient in NE Spain - VILLAR-SALVADOR, P (Trees-Structure and …, 1997)
Stem xylem features in two evergreen Quercus species (Q. coccifera and Q. ilex) and a deciduous one (Q. faginea) were analysed along an Atlantic-Mediterranean climatic gradient in which rainfall and winter cold experi- ence strong variation. Mean maximum vessel diameter, vessel density, vessel element length, xylem transverse sectional area, Huber value (xylem transverse sectional area per leaf area unit), theoretical leaf specific conductiv- ity (estimated hydraulic conductance per leaf area unit) and total leaf area were determined in 3-year-old branches. Q. faginea presented the widest vessels and the highest theo- retical leaf specific conductivity while Q. coccifera showed the lowest total leaf area and the highest Huber value. Studied features did not exhibit significant correlations with mean minimum January temperature in any species but did show significant relationships with rainfall. In Q. coccifera, mean maximum vessel diameter, vessel element length and theoretical leaf specific conductivity increased with higher rainfall while vessel density decreased. Mean maximum vessel diameter and total leaf area in Q. ilex increased with precipitation whereas variables of Q. faginea did not show any significant trend. Results suggest that aridity, rather than minimum winter temperature, controls stem xylem responses in the studied evergreen species. Q. faginea traits did not show any response to precipitation, probably because this species develops deep roots, which in turn makes edaphic and topographic factors more important in the control of soil water availability. In response to aridity Q. coccifera only exhibits adjustment at a xylem level by reducing its water transport capacity through a reduction of vessel diameter without changing the amount of xylem tissue or foliage, whereas Q. ilex adjusts its water transport capacity in parallel to the foliage area.
Keywords: huber value; Mediterranean climate; rainfall gradient; winter temperature; wood anatomy

NATURAL GERMINATION AS RESILIENCE COMPONENT IN MEDITERRANEAN COPPICE STANDS OF CASTANEA-SATIVA MILL AND QUERCUS-ILEX L - Bacilieri, R; Bouchet, M A; Bran, D; Grandjanny, M; Maistre, M; Perret, P; Romane, F (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1994)
In the Mediterranean basin, most of the present forests derive from original forests where the dominant species was different from the present one. These changes are largely due to human activities reflecting millenia of management and, often, overexploitation. In southern France, for example, palaeoecologists believe that the original malacophyllous deciduous forest of downy oak (Quercus pubescens) was replaced by a sclerophyllous evergreen holm oak (Quercus ilex) coppice in the driest areas, and chestnut (Castanea sativa) orchards or coppices in the `'wettest'' areas. However, for the last several decades, exploitation of these coppice stands has been decreasing. In this study, we addressed the question of the resilience of these managed ecosystems in the fact of changing management schemes, and to determine appropriate strategies and criteria of sustainable development. We present some aspects of the auto-succession after clearcutting of holm oak coppice stands and aspects of the natural regeneration of 4 species (Q. ilex, Q. pubescens, C. sativa, and P. pinaster). The consequences of the contrasted life history strategies are compared to estimate the future of these coppices.
Keywords: ABANDONED LAND; CASTANEA-SATIVA MILL; Coppice stands; germination; Mediterranean climate; Regeneration

Comparative genet survival after fire in woody Mediterranean species - López-Soria, L; Castell, Caries (Oecologia, 1992)
Using data from three fires in northeastern Spain, we tested a condition necessary to support the idea that fire has been a factor in the evolution of the res- prouting habit: populations of all resprouting species within a community should show high levels of genet survival after fires and show a low coefficient of varia- tion. Species with high mean survival values were: Quer- cus ilex L., Phillyrea latifolia L., and Viburnum tinus L., with 88, 86 and 83% survival respectively; these groups had resprouts emerging from rootcrowns. Then followed Arbutus unedo L. (75%), Pistacia lentiscus L. (73 %), Erica arborea L. (77 %), Erica multiflora L. (57 %) and Juniperus oxycedrus L. (55%). This last group had resprouts from lignotnbers or burls. These two groups also differed in the variability around the mean: the first showed a lower coefficient of variation, 6-12, and the second ranged from 19 to 26. Slope exposure had no significant in- fluence on the process of resprouting, but soil depth did, with precipitation as a covariate. In the shallow soil category, the difference in genet survival between south- ern and northern exposures was 14% (71% vs. 57%); while the difference in the deep soil category was low, 5 % (87% vs. 82%). There was no significant interaction. The component of variance for soils was larger than that for species-specific effects; substantial overlap of the within- species variance indicated that species responded as if they were a single hypothetical population, in which most of the variation in chances of survival was due to the soil conditions. The possession of the resprouting habit did not ensure a high performance. Hence, we find weak support for fire as a factor in the evolution of the res- prouting habit.
Keywords: evolutionary convergence; fire-adapted trait; Mediterranean climate; regenerative types; resilience

Dynamics of holm oak (Quercus ilex L.) coppices after clearcutting in southern France - Floret, C.; Galan, M. J.; Floc'h, E.; Romane, F. (Plant Ecology, 1992)
Holm oak (Quercus ilex L.) forest is one of the most widespread biocoenoses in the southern part of France. Until recently, clearcutting of wood for domestic use was carried out every 20 years or so in these coppice stands. In order to study coppice stand dynamics after cutting this paper presents results of observations of some items describing the vegetation structure, the floral composition, and the life cycles in a holm oak coppice stand during a six year period after clearcutting. One of the questions addressed in this study was whether these coppice stands reach a 'steady' state based on auto-succession, or if they continue to change. The results of the floristic changes after cutting suggest that the model of auto-succession best fits with the vegetation dynamics, even if changes in the density and life cycles of herbaceous species still exist six years after clearcutting.
Keywords: Life cycles; Mediterranean climate; vegetation succession

Factors affecting radial growth of Quercus ilex L. in a coppice stand in southern France - Cartan-Son, M.; Floret, C.; Galan, M. J. (Plant Ecology, 1992)
Quercus ilex woodlands in the south of France are characterized by low productivity. Several hypo- theses have been put forward to provide an explanation for this phenomenon: (i) senescence of coppice stumps; (ii)limited availability of water and nutrient resources; (iii)intershoot and inter-plant compe- tition. To test some of these hypotheses, growth response to rainfall distribution and nutrient supply (NPK), and the influence of edge effects after clear-cutting were studied in a 40-yr old stand. Curves of radial increment were compared with precipitation and umbrothermic patterns for the 6 years studied. Water availability apparently accounted for some inter-annual differences in growth. However, it was not mean annual rainfall, but rather rainfall occurring in late spring-summer (June, July) which played a large role in determining radial growth. Radial growth was also increased by nutrient supply. Its positive effect was strengthened by favourable rainfall in 1987. Edge-effects following a clear-cut were also found, both in the first year and in four succeeding years following the cut. This comprised in greater radial growth rate for all shoots, with reduced repression of smaller shoots by the larger ones. The effect decreased over a distance of 10 m with increasing distance from the cut field. This could be explained by increased availabiDLy of water, nutrient resources, and light.
Keywords: clear-cutting; edge effect; Mediterranean climate; nutrient supply; productivity

NATURAL DEGENERATE MEDITERRANEAN FORESTS - WHICH FUTURE - THE EXAMPLES OF THE HOLM OAK (QUERCUS-ILEX L) AND CHESTNUT (CASTANEA-SATIVA MILL) COPPICE STANDS - Romane, F; BACILLIERI, R; Bran, D; Bouchet, M A (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Primarily derived from the Quercus pubescens forest destroyed by overexploitation, the Quercus ilex and Castanea sativa coppice stands are two of the most widespread biocoenoses in the European Mediterranean area. Two of the questions we sought to answer were (i) in the case where the same disturbance persists, whether these coppice stands reach a state of “equilibrium” based on auto-succession or they continue to change, and (ii) in the case where disturbance stops, whether the present dominant species (Q. ilex or C. sativa) continues to be dominant (high resilience) or an other species (Q. pubescens ?) could replace it. A third case exists, i.e. a change of the “disturbance” in order to obtain a “sustainable” development, but, in that case, biological or socio-economical criteria must be defined. In order to highlight the first stages of these possible changes, germination abilities of these species were studied and compared. For Q. ilex coppice stands, it can be said that there would appear to be a partial allelopathic inhibition of Q. ilex germination, to which Q. pubescens is less sensitive. For C. sativa, this phenomenon was not found. We also briefly discuss the main characteristics of a programme which tests some biological criteria for a sustainable development.
Keywords: CASTANEA-SATIVA MILL; COPPICE STAND; management; Mediterranean climate; NATURAL DEGENERATE FOREST; QUERCUS-ILEX L; QUERCUS-PUBESCENS WILLD; sustainable development; Vegetation dynamics

Notes on Quercus ilex L. in Liguria (NW Italy) - Barberis, G.; Peccenini, S.; Paola, G. (Plant Ecology, 1992)
The climatic characteristics of the Liguria region have been outlined by means of raw data and derived indices (water balance related to potential evapotraspiration, Rivas-Martinez's index of mediterraneity and thermicity, De Martonne's index of dryness, and Emberger's pluviothermic quotient and index of summer dryness). Their interpretation suggests that Liguria is a boundary region between two different climatic areas: the Mediterranean and that of Central Europe. The distribution of Quercus ilex communities in Liguria have suffered the heavy consequences of human activity on the coastal belt of the region. There is, however, sufficient evidence to show that their presence is closely linked to climatic conditions. Quercus ilex communities are absent from the western coastal belt where the annual water balance is below -50 mm and high mean temperatures occur. They are also absent from marly limestone dominated areas where annual water balance is below 300 ram. Quercus ilex woods show a preference for water balance values between 0 and 600, with the better de- veloped forests being found in central and eastern coastal Liguria. The Ligurian Quercus ilex woods are ascribed to Quercetum ilicis Br.-BI. 1915. Given that the pres- ence within their floristic composition of a group of species of Querco-Fagetea (more species in eastern stands, few in western ones) is an almost constant characteristic, the subass, fraxino-ostryetosum Mariotti 1984 can be retained for many of them. Quercus ilex is not present in the initial succession stages of Mediterranean Liguria vegetation. It can be found in later stages when the vegetation is more fully de- veloped towards a maquis type structure. In this case it tends to become dominant and the community develops (if no fire or other human interference occurs) into a Quercus ilex forest. Frequently, this succession takes place under an old tree layer cover (generally Pinus sp.), a remnant of man's past management of the vegetation in the area.
Keywords: Mediterranean climate; quercus ilex communities; quercus ilex ecology

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration

Variations de la croissance radiale de Quercus ilex L en fonction du climat - Zhang, S H; Romane, F (Ann. For. Sci., 1991)
Diameter growth of Quercus ilex L and the interannual variability of climatic characteristics. Diameter growth of Quercus ilex L, the dominant sclerophyllous species in much of the Mediterranean basin vegetation, was studied in relation to precipitation and temperature. The study site in Montpellier (Southern France) has a Mediterranean climate. Eleven trees, grown from acorns in 1963, were cut in 1984 and the rings studied at 3 levels (ground, 0.5 and 1 m above the ground). The data were analyzed by the ARMA procedure which gives the part of the total variation due to the autocorrelation processes. A multiple regression between the factors of a principal component analysis (PCA) of the monthly climatic data (rainfall and temperature) and the residuals issuing from the ARMA procedure then suggested that the large annual rings were due to a particular rainfall distribution during the year, the late summer precipitation promoting a large annual growth diameter (table II). The presence or absence of false rings (table I) was also analyzed by PCA (figs 2 and 3). The false rings were positively correlated to a large annual growth diameter corresponding to a high summer rainfall (fig 4), while the relationship with the temperature preceding the growing season was negative. It therefore appears that this species is relatively unaffected by spring climatic conditions, ie which generally indicate the main growth phase, but that it is able to take advantage of the interannual climatic variations of the region.
Keywords: diameter growth; Mediterranean climate; Precipitation; Quercus ilex L; ring; Temperature

Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice - Bran, D; Lobreaux, O; Maistre, M; Perret, P; Romane, F (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.
Keywords: dynamics; Mediterranean climate; Southern France; succession

Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example - Floret, C; Galan, N J; Floc'h, E; Orshan, G; Romane, F (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.
Keywords: coppice; growth form; Life form; Mediterranean climate; Quercus ilex L; Southern France